Characterization of Municipal Solid Waste in the Federal Capital, Abuja, Nigeria (Global Journal of Science Frontier Research, 2014)
Municipal solid waste management has emerged as one of the greatest challenges facing environmental protection agencies in developing countries. This paper presents a characterization study of the municipal solid waste generated in the Federal Capital Territory, Abuja, Nigeria. The characteristics of the municipal solid waste were determined in terms of the components, average mass (kg) and percentage generated per district. It was found that 56.20%/52.0% of the solid waste generated in the area is made up of food/ petrucsible; rubber 10.20%/3.56%; paper 10.00%/ 12.46%; glass/ceramics 7.60%/1.42%; plastics 7.4%/2.85%; metals 2.60%/0.71% and other forms of waste 5.60%/25.62% (dust particle, Ash, stones) for wet and dry seasons respectively and the waste generation rates ranged from 0.59 to 0.79 kg/capita/day. The AEPB is faced with constraints like lack of institutional framework, inadequate budgetary provision, lack of institutional framework, inadequate bylaws and regulations and insufficient information on the quantity and composition of the solid waste. It is suggested that adequate financial provision, proper waste legislation, training and re-training of staffs and community full participation in waste management be encourage while formal composting and recycling facilities should be setup.
Keywords: characterisation; municipal solid waste; abuja; composting; recycling